2015
DOI: 10.5539/ijps.v7n3p130
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Strategy Training Adds to the Effects of Working Memory Training in Children with Special Educational Needs

Abstract: The effects of computer-based Working Memory (WM) training using two training procedures were examined among sixty-four primary-school children with Special Educational Needs (SEN). Measures of general cognitive ability, auditory and visuospatial working memory, arithmetic ability, and reading and writing skills were gathered and analysed. The referred group of SEN children predominantly had lower performance in auditory WM, arithmetics and reading and writing skills. The SEN children within respective school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…The results showed that the referred group of SEN children scored somewhat low on FR and particularly low on measures of both WM and Planning, suggesting that WM and complex EF are cognitive functions challenged in children with SEN. This is in line with previous studies showing that low WM as well as problems with EF are common among children with SEN (Alloway et al, 2005;Partanen et al, 2015;Pickering & Gathercole, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that the referred group of SEN children scored somewhat low on FR and particularly low on measures of both WM and Planning, suggesting that WM and complex EF are cognitive functions challenged in children with SEN. This is in line with previous studies showing that low WM as well as problems with EF are common among children with SEN (Alloway et al, 2005;Partanen et al, 2015;Pickering & Gathercole, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Since reviews of WM training (Melby-Lervåg & Hulme, 2012) have shown that WM training effects tend to be short-termed and transference to school subjects is rare, addressing more complex EF by training planning and metacognitive strategies could be a future direction, particularly in mathematical problem-solving. This has also been explored in a recent study, where complex EF was addressed by adding components of planning and metacognitive strategy training into WM training in school (Partanen et al, 2015). In a review of WM and EF training, it has also been proposed that there is a need for more process-based training regimens (Titz & Karbach, 2014).…”
Section: Conclusion Limitations and Implications For Practicementioning
confidence: 99%
“…A randomized controlled study on children with Down syndrome conducted by Bennett (Bennett et al, 2013 ) showed that WM training (Cogmed 10–16-week period at school; three times a week for 25 min per session), produces NT and the effects were maintained at a 4-month follow-up. Partanen et al ( 2015 ) demonstrated in a randomized controlled trial that WM training in combination with metacognitive techniques produced a significant difference in WM maintained at a 6-month follow-up. No transfer to arithmetic or reading and writing skills occurred in any of the two training conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Such mixed results are also apparent on academic outcome measures following Cogmed, with participants showing no improvement on academic achievement and classroom performance measures compared to controls in numerous reports (Bigorra et al 2016;Chacko et al 2014;Dunning et al 2013;Gray et al 2012;Partanen et al 2015;Roberts et al 2016;van der Donk et al 2015; van Dongen-Boomsma et al 2014). Although researchers have proposed other explanations for the lack of far transfer to academic performance following Cogmed (Bergman Nutley and Söderqvist 2017), it is worth noting that studies in which there has been non-significant far transfer to academic achievement are almost exclusively rigorously designed, randomized trials with active control groups.…”
Section: Working Memory Training Backgroundmentioning
confidence: 97%